The Results of a New Distal Protection Method in Intervention for Chronic Total Occlusion of the Superficial Femoral Artery - Tomoko Kobayashi; Atsushi Funatsu; Emiko Ejima; Hiromi Muranishi; Makoto Utsunomiya; Kensaku Shibata; Masahiro Mizobuchi; Yoshihisa Enjoji; Shigeru Nakamura (Cardiology Research and Practice)
Aims. To determine the efficacy of a new distal protection method in SFA CTO interventions. Methods and Results. From June 2003 to February 2009, ninety-two consecutive, chronic total occlusions of superficial femoral arteries were treated with catheter-based intervention using a bidirectional approach. Nine of these cases were managed with our original, distal protection method, based on symptoms, angiographic images, wire resistance, and intravascular ultrasound images. The average age was 73 years; eight patients were male. The mean occlusion length was 17.1 cm. A distal protection balloon was inserted from the retrograde sheath in the popliteal artery and placed distal to the occluded lesion after successful wire crossing. Lesion dilatation with a balloon was performed antegradely and debris was removed by 6Fr. guiding catheter. Debris was retrieved from all lesions, consisting mainly of thrombus. Where we decided not to use the distal protection method, there was no distal thromboembolism. Conclusion. In SFA-CTO intervention, the risk of distal embolization is 10%, which can be anticipated and eliminated by the distal protection method.